Pengaruh Kredit Sektoral terhadap Pertumbuhan Ekonomi Provinsi Kalimantan Selatan - Norhidayah (PPJP ULM, 2018)
The purpose of this research is to know the effect of credit distribution of theagricultural sector, mining, construction, and processing industry on the economicgrowth of South Kalimantan.The method of analysis performed is a multiple linear regression of paneldata. This study uses observations of 5 years from 2012 to 2016; the available data isprocessed using the computer program aids E-views 9.0Based on the results of the research, in the outcome, agricultural creditdisbursement has a negative and significant effect on the economic growth of SouthKalimantan. The lending of the mining sector has a negative and insignificant impacton the economic development of South Kalimantan. The borrowing of the constructionsector has a positive and significant impact on the economic growth of SouthKalimantan. The credit distribution of the manufacturing industry has a negative andsignificant effect on the economic development of South Kalimantan.